Oxidative Coupling Reaction for Micro Trace Analysis of Mebendazol Residual with p-bromoaniline in Presence of n- bromosuccinimide - Takleef Sallal; sumayha Abbas (مجلة بغداد للعلوم)
Rapid, reproducible and accurate method has been developed for the assay for of mebendazol (MBZ) residual assay. The method is based on alkaline hydrolysis of MBZ with sodium hydroxide then oxidation with N-bromosuccinimide (NBS) followed by coupling with 4-Bromoaniline (4-BA) to yield a highly colored product absorbed at maximum 434 nm. Regression analysis of linearity range was found (0.6-2.8) µg.ml-1.  The optimum conditions that affect the oxidation were studied. The developed method was found to be precise with mean value of relative standard deviation (1.153- 1.303) and accurate with relative error (-0.5940-1.7821) .The calculated molar absorptivity and sandal sensitivity values of (29825 L.mol-1.cm-1), 0.0099 µg.cm-2 respectively.  The limit of detection and limit of quantitation were of 0.04696, 0.156548 µg.ml-1 respectively .The suggested method showed good recovery with a mean value of 100.77% for analysis of dosage forms.